The Political Economy of Biotechnology - David Zilbermann; Gregory Graff; Gal Hochmann; Scott Kaplan (German Journal of Agricultural Economics (GJAE), 2015)
The introduction of GE to agriculture has encoun-tered strong resistance, reflecting conflicting groups within and between countries. This has resulted in a regulatory environment that has limited the application of GE mostly to feed and fiber and practically restricted its application in food. While agricultural biotechnology has already provided significant benefits, much of its potential has not been reached. Regulation of agricultural biotechnology reflects conflicting interests and varying political power of different groups. The relatively supportive regulation of biotechnology in the U.S. reflects that it is an American technology, and supporting groups like the farm lobby, technology manufacturers, and U.S. consumers outweigh the objections of environmentalists and other opposition to the technology. In Europe, growing concern about environmental side-effects of agriculture, the fact that GE technology was imported, and the power of environmental groups has resulted in restrictive regulation. To a large extent, the fate of GE depends on the level of goodwill it generates among voters, and as long as a large segment of the population is apprehensive about its benefits, heavy restrictions about the technology that prevent it from reaching its potential will persist.
Keywords: 330